Weight gain after adjuvant chemotherapy in patients with early breast cancer in Istanbul Turkey - DANE, FAYSAL; YUMUK, PERRAN FULDEN (HUMANA PRESS INC, 2011)
Weight gain is a well-known and unwanted complication of adjuvant chemotherapy in breast cancer. We observed that the female Turkish cancer patients frequently gain weight with adjuvant treatment of breast cancer and planned to examine the magnitude of this problem in early breast cancer patients treated at our hospital. A total of 176 early breast cancer patients who received their adjuvant systemic therapy in Marmara University Hospital between 2003 and 2007 are included in the study. We recorded their weight before and after chemotherapy and also a year after chemotherapy to find out whether the change with weight is transitory. We have also recorded demographic information, including the educational level, menopausal status, the type of chemotherapy or hormonal treatment administered stage of disease, marital status, occupation and the underlying diseases to analyze the relationship between change in weight and these parameters. Median age of patients was 53 and 72% of patients were postmenopausal. Educational level was equally distributed for primary education (27%), high school (40%), and university (33%). The majority of the patients (76%) was married, had two children (69%) and was housewife (60%). Family history of any cancer was high (32%). Most of the patients had stage II cancer (56%), received anthracyclines+/- taxane based chemotherapy (98%) and had no underlying disease (68%). The majority also did not smoke (73%) or drink alcohol (93%). A total of 67% and 72% patients gained weight upon completion and one year after completion of chemotherapy. Mean weight before the chemotherapy, upon completion of chemotherapy and one year after completion of chemotherapy were 68.9 kg, 70.6 kg (P = 0.000) and 71.9 kg (P = 0.000) respectively. Mean body mass index was 27.1 at baseline, 27.8 upon completion of chemotherapy (P = 0.000) and 28.3 one year after completion of chemotherapy (P = 0.000). Age, menopausal status, multiparity and presence of comorbid diseases had statistically significant impact on weight gain following adjuvant therapy in breast cancer patients (P = 0.000, P = 0.008, P = 0.015 and P = 0.017 respectively). This study shows that Turkish women with early breast cancer gain weight after adjuvant systemic therapy, in line with European and American counterparts. This increase in weight is maintained at least one year after adjuvant therapy. Given the adverse consequences of weight gain in terms of both breast cancer prognosis and general health, it is necessary to inform patients about this change and to develop strategies for weight maintenance during and after systemic therapy.
Keywords: Chemotherapy; Breast cancer; Adjuvant treatment; Weight gain; BODY-MASS; PHYSICAL-ACTIVITY; DIAGNOSIS; WOMEN; OBESITY; SURVIVAL; TAMOXIFEN; THERAPY; LIFE; PREMENOPAUSAL